Acidic hierarchical zeolite ZSM-5 supported Ru catalyst with high activity and selectivity in the seleno-functionalization of alkenes. Issue 36 (19th April 2017) - Dong, Hai; Zhang, Lei; Fang, Zhongxue; Fu, Wenqian; Tang, Ting; Feng, Yu; Tang, Tiandi
Abstract : The acidic hierarchical zeolite ZSM-5 (HZSM-5-H) was synthesized for preparation of a supported Ru catalyst that was applied in the eleno-functionalization of alkenes with high efficiency. Abstract : The acidic hierarchical zeolite ZSM-5 (HZSM-5-H) was synthesized for the preparation of a supported Ru catalyst (Ru/HZSM-5-H). The obtained Ru/HZSM-5-H catalyst shows high activity and product selectivity in the seleno-functionalization of alkenes compared to γ-Al2 O3, basic ETS-10 and acidic microporous zeolite ZSM-5 supported Ru catalysts (Ru/γ-Al2 O3, Ru/ETS-10 and Ru/HZSM-5, respectively), as well as a homogeneous RuCl3 catalyst. The relatively strong acidic sites in Ru/HZSM-5-H could benefit the adsorption of styrenes and the activation of the CC bond. Meanwhile, Ru 4+ in Ru/HZSM-5-H could facilitate the formation of electrophilic selenium species as compared to Ru 0 species. In addition, the Ru/HZSM-5-M catalyst exhibits broad substrate compatibility in the difunctionalization of alkenes.